Trendovi u skrbi za osobe starije životne dobi u Republici Hrvatskoj i u zemljama Europske unije - Žganec, Nino (Array, 2008)
Starting from the basic demographic trends, with the share of persons older than 65 years of age of 15.7%, Croatia matches the average of the EU member states. Since ageing of the population represents one of the greatest challenges that the world is faced with, the position of the elderly in society, quality of life in the older age and trends in the policy of care for the elderly are the matter of interest of political, professional and scientifi c-research circles of the largest number of the developed countries in the world. The analysis of the trends in the care for the elderly in EU member states, as well as in the Republic of Croatia, indicates the promotion of healthy and active ageing, which is regarded as the key for ensuring an equal role of the persons of the third age in society. A common strategy for most policies of care for the elderly in European countries includes strengthening of the community care, in the sense of developing non-institutional forms of care. Namely, unlike the trends in European countries, where the policy of care for the elderly is increasingly focused on provision of help in their homes, in an attempt to keep elderly persons in their own homes, the trends in the care for the elderly in the Republic of Croatia only partly follow the ones on the level of the EU due to insuffi cient development of local forms of management of systems of the care for the elderly, inadequate network of the institutional forms of care, underdeveloped and insuffi ciently clear systems of fi nancing and so on. Ageing changes society in important and fundamental elements of its functioning, and demands a complex assessment and reorganisation of the economic and social political framework